2018
DOI: 10.1155/2018/6234931
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Change in Metabolic Capabilities of Sediment Microbial Communities in River and Lake Ecosystems

Abstract: Information on the biodegradation potential of lake and river microbial communities is essential for watershed management. The water draining into the lake ecosystems often carries a significant amount of suspended sediments, which are transported by rivers and streams from the local drainage basin. The organic carbon processing in the sediments is executed by heterotrophic microbial communities, whose activities may vary spatially and temporally. Thus, to capture and apprehend some of these variabilities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 57 publications
7
13
0
Order By: Relevance
“…PCA revealed the seasonal pattern in BWC microbial community structure, and variations in the drivers of ecosystem change such as percent moisture content, temperature, and C/N ratios supported the PCA ndings. Our study extends other reported shorter-term and annual cycle studies of seasonal variations in microbial communities (Smoot and Findlay 2001;Brummer et al 2002;Sekiguchi et al 2002;Feris et al 2003;Oest et al 2018).…”
Section: Spatial and Seasonal Variations In Microbial Biomasssupporting
confidence: 91%
“…PCA revealed the seasonal pattern in BWC microbial community structure, and variations in the drivers of ecosystem change such as percent moisture content, temperature, and C/N ratios supported the PCA ndings. Our study extends other reported shorter-term and annual cycle studies of seasonal variations in microbial communities (Smoot and Findlay 2001;Brummer et al 2002;Sekiguchi et al 2002;Feris et al 2003;Oest et al 2018).…”
Section: Spatial and Seasonal Variations In Microbial Biomasssupporting
confidence: 91%
“…These substrates are naturally occurring as products of the bacterial degradation and photochemical degradation of the organic matter in surface waters [64,65]. The prompt ability (24 h) in the utilization of complex polymers (tween 80) might indicate the presence of organic pollutants in altered groundwater, being this functional trait linked to polluted environment [55,63]. In this study, organic pollutants were detected at low concentration in some of the altered groundwater sites [25].…”
Section: Discussionmentioning
confidence: 61%
“…The delay in utilizing tween 80 may reflect the metabolic plasticity [54] that modulates the microbial community functions, suggesting a higher sensitivity of pristine communities to contingent events of contamination by anthropogenic organic pollutants. The shift toward the utilization of amines in the pristine condition might indicate the presence of opportunistic classes of bacteria and a condition of nitrogen deprivation [37,55]. Unlike C-enriched substrates (i.e., carbohydrates and polymers), amines are enriched in nitrogen and utilized by bacteria to synthetize organic molecules such as amino acids and proteins [56].…”
Section: Discussionmentioning
confidence: 99%
“…We have observed a different carbon utilization pattern for each water samples. This may be due to the difference in the water quality, which nurtures diverse structure, the composition of microbial communities based on the nutrients [50,51] and other physic-chemical characteristics. The microbial communities based on carbon substrate utilization showed interesting results for instance, in Ganga, the samples from Alaknanda to Haridwar (G2 to G5) clustered together demonstrating that river Ganga gets most of its attributes from the source stream Alaknanda.…”
Section: Discussionmentioning
confidence: 99%